Prospects of Cloud AI, Automation, and Edge Computing in Oracle Integration Frameworks - Salve, Sonba (Journal of Research in Science and Engineering, 2025)
The rapid evolution of cloud technology, particularly within the Oracle Cloud ecosystem, is being shaped by key innovations such as AI - driven automation, event - driven integration, and IoT - enabled edge computing. As enterprises increasingly adopt cloud - first strategies, intelligent automation is streamlining workflows, enhancing system reliability, and enabling predictive decision - making. Oracle Cloud Integrations are evolving through AI - powered data processing, natural language interfaces, and proactive monitoring, which optimize performance and reduce operational complexity. Additionally, hybrid cloud approaches and low - code development tools are minimizing migration risks while ensuring seamless integration with legacy systems. To maximize ROI and agility, organizations must adopt scalable, AI - driven cloud strategies that align with business goals and industry - specific needs. As sustainability becomes a critical focus, cloud providers must prioritize energy - efficient data centers and carbon - neutral initiatives to support a responsible and sustainable digital transformation.